2021
DOI: 10.1093/nar/gkab644
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of the nucleosome core particle containing Giardia lamblia histones

Abstract: Giardia lamblia is a pathogenic unicellular eukaryotic parasite that causes giardiasis. Its genome encodes the canonical histones H2A, H2B, H3, and H4, which share low amino acid sequence identity with their human orthologues. We determined the structure of the G. lamblia nucleosome core particle (NCP) at 3.6 Å resolution by cryo-electron microscopy. G. lamblia histones form a characteristic NCP, in which the visible 125 base-pair region of the DNA is wrapped in a left-handed supercoil. The acidic patch on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 73 publications
2
15
0
Order By: Relevance
“…1), the structure exhibits remarkable conservation of overall histone fold architecture. This is consistent with structures from other divergent organisms such as the parasite Giardia lamblia 56 , the archaeon Methanothermus fervidus 57 , or the Marseilleviridae 48,58 giant viruses. However, subtle differences in histone packing and specific histone amino acid substitutions give rise to properties unique to the T. brucei NCP.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…1), the structure exhibits remarkable conservation of overall histone fold architecture. This is consistent with structures from other divergent organisms such as the parasite Giardia lamblia 56 , the archaeon Methanothermus fervidus 57 , or the Marseilleviridae 48,58 giant viruses. However, subtle differences in histone packing and specific histone amino acid substitutions give rise to properties unique to the T. brucei NCP.…”
Section: Discussionsupporting
confidence: 83%
“…2-4). Chromatin arrays constructed from other nucleosomes with DNA end flexibility 46,56,62 were also found to favour more open chromatin conformations, particularly due to alterations in inter-nucleosomal DNA path 62 . Future experiments on chromatin arrays would help explore if entry/exit DNA flexibility described here could explain the more open chromatin in T. brucei.…”
Section: Discussionmentioning
confidence: 96%
“…These observations are in line with recent structural studies of other histone variants. Particularly, Sato et al [ 69 ] have shown that nucleosomes based on histones from G. lamblia demonstrated outward bending of the H2A α2-helix. Concomitantly, Zhou et al [ 33 ] observed that H2A.B-containing nucleosomes had a 15° kink in the C-terminal region of the H2A.B α2-helix, although this kink was more in the direction along the nucleosomal superhelical axis.…”
Section: Discussionmentioning
confidence: 99%
“…The cryo-EM structure of the G. lamblia nucleosome was determined at a 3.6 angstrom resolution, after reconstitution with 145 base pairs of modified Widom 601 (601L) palindromic DNA [ 61 ]. The overall structure of the G. lamblia nucleosome resembles that of the human nucleosome ( Figure 2 A).…”
Section: Structures Of Nucleosomes Containing Parasite Histonesmentioning
confidence: 99%